PENGARUH MODEL PEMBELAJARAN TIPE HOTS TERHADAP KETERAMPILAN SOSIAL DAN HASIL BELAJAR PKN - Nizmi Putri (Nusantara Hasana Journal, 2022)
The learning model of the high order thinking skills type is a model that not only tests the ability to remember, understand, and apply, but the high order thinking skills model tests the ability to analyze and evaluate. The Problem Based Learning Model is one of the HOTS Type learning models that can be used to analyze students' social skills and evaluate student learning outcomes. This can be seen in Civics learning in class IV SDN101788 MARINDAL. Especially in the matter of Globalization in the environment, it is very necessary for students to understand what is meant by globalization, the negative impacts and positive impacts of globalization, so that students not only understand that globalization is the process of entering to the scope of the world, but also students can clearly understand the benefits, advantages and disadvantages of globalization. The use of the HOTS type learning model can help students to understand properly and make students trained to think at the analytical level. so that researchers are interested in conducting a study using this learning model. The purpose of the study was to determine the effect of the Problem Based Learning model in analyzing students' social skills and evaluating student learning outcomes. The data source was obtained from the fourth grade teacher document at SDN 101788 MARINDAL 1 for the 2021/2022 academic year. The results showed that the high-order thinking skills learning model requires high-level thinking so that it can make students trained to think at the level of analyzing students' social skills and evaluating student learning outcomes.